Pemanfaatan Aplikasi Quizizz Dalam Sistem Informasi Asesmen Sumatif Di SMPN 1 Amali Kabupaten Bone - Eka Sulistiawati,; Muljono Damopolii,; Mardhiah Hasan (Institusi Agama Islam Negeri (IAIN) Bone, 2024)
The purpose of the mini research is to find out the utilization of the quiz application in managing the summative assessment information system, researchers use qualitative methodology by observing and describing the object under study in the field specifically and in detail. Data collection researchers use observation, interview, and documentation methods.Â Important findings from the research show that the quizizz application is an application that makes it easy for educators to check student performance results, facilitate archiving of lesson questions and student work effectively, quickly and the results are accurate. The quizizz application is still detected using a new application, so teachers are required to adjust to new features and improve their abilities. Meanwhile, the implementation of summative assessments manually is not very effective because some students are less careful in working on the questions given due to the monotonous appearance of the questions and paper, as well as the process of educators checking student answer sheets which takes a long time to check one by one so that the process of inputting their scores can be hampered.Â In conclusion, the utilization of the quiz application is in accordance with applicable regulations and the implementation of summative assessment needs to be improved with interesting implementation methods and media,